2007
DOI: 10.1111/j.1365-2648.2007.04443.x
|View full text |Cite
|
Sign up to set email alerts
|

Staffing adequacy, supervisory support and quality of care in long‐term care settings: staff perceptions

Abstract: The perception of adequate staffing and of sufficient supervisory support, especially empowering support increases the probability of perceiving the care quality as good. If supervisors concern themselves with staff members' perceptions, they can better identify the staffing needs and also the support needs of personnel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 38 publications
5
35
1
Order By: Relevance
“…Previous studies have shown that quality of care is related to staff's well-being [50] and job satisfaction [51,52] The staff that indicated they had greater time to perform their duties also perceived the quality in the secure-environment dimension as higher in this study. This finding is in line with Bowers et al [53], who found that time available for giving care has an impact on quality of care.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Previous studies have shown that quality of care is related to staff's well-being [50] and job satisfaction [51,52] The staff that indicated they had greater time to perform their duties also perceived the quality in the secure-environment dimension as higher in this study. This finding is in line with Bowers et al [53], who found that time available for giving care has an impact on quality of care.…”
Section: Discussionmentioning
confidence: 48%
“…This finding is in line with Bowers et al [53], who found that time available for giving care has an impact on quality of care. In addition, Räikkönen et al [51] argue that staff with sufficient time performed work of better quality than those with insufficient time.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary Traumatic Stress was negatively correlated with supervisory support (p=.002), but after effect size was calculated the strength of association was not as strong as organizational support and trauma-informed caregiver development.This does not negate the importance of supervisory support as this study found supervisory support to be significantly associated with higher levels of compassion satisfaction (p < .001) and the strength of this relationship was medium when effect sizes were calculated. Countless other researchers have found lack ofsupervisory support to be a strong predictor of burnout and secondary traumatic stress (Harrison & Westwood, 2009;Jankoski, 2010;Tehrani, Osborne, & Lane, 2012) and correlated with trauma caregiver perceptions of client care (Räikkönen, Perälä, &Kahanpää, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Positive managernurse relationships, [3] and managers providing support and empowering work environments to their nurses are strongly associated with nurses' self-assessed skills to deliver high quality care, [5] whereas unjustified management behaviour decreases nurses' work motivation. [3] Managers also need to recognize their own resources and shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Due to the issues related to quality care and patient safety, added with the global shortage of professionally qualified nurses, interest in nurses' competence has in-creased. [3][4][5] Consequently, assessment of competence is important in targeting available competence resources in an optimal way. [3] It is also important that nurses' and their managers' competence assessments are realistic and aligned.…”
Section: Introductionmentioning
confidence: 99%